Pemanfaatan Sampah Plastik di Desa Pongangan Menjadi Ecobrick - Silviana, Silviana; Lilik Rochmah, Lilik Rochmah; Suprastiyo, Suprastiyo; Wahyuni, Titik; Firnanda, Irma; Rahmawati, Siti; Prakarsah, Sandy; Aulia, Dwyky Hizbul; Sa’adah, Niltis; Angraini, Dwi Ayu; Ikhtisholiyah, Ikhtisholiyah (GOTAVA Pengabdian Kepada Masyarakat, 2024)
The biggest waste in Indonesia is plastic waste, even though the government has stopped using plastic bags in minimarkets, plastic waste is still the biggest waste in Indonesia. One way to handle plastic waste is by recycling, such as recycling plastic bottles through ecobricks. Ecobricks themselves are to overcome the problem of plastic waste by collecting, cleaning and packaging plastic into very dense plastic bottles. Its function is to extend the life of the plastic by processing it into something that can be used or is useful. The method used is counseling in the form of socializing ecobricks in the form of chairs which will be socialized on how to make and use them in the Pongangan Rejo area, Manyar District, Gresik Regency with the aim of the community being creative and innovative in utilizing plastic waste and protecting the surrounding environment. The results obtained are that the community can make good use of plastic waste, and are able to make ecobrick products in the form of chairs or anything else, both for personal needs and for the surrounding community.